2331. Household Pets and Recovery of Moraxella catarrhalis and Other Respiratory Pathogens From Children With Asthma. (26th November 2018) - Davis, Meghan; Dalton, Kathryn; Johnson, Zoe; Ludwig, Shanna; Sabella, Katie; Newman, Michelle; Whaley, Susan Balcer; Keet, Corinne; McCormack, Meredith C; Carroll, Karen C; Matsui, Elizabeth C
Abstract: Background: Upper respiratory tract colonization with a number of bacterial pathogens has been associated with significant respiratory disease and asthma in children. As part of a larger study to evaluate microbial contributions from animals to children with asthma, we tested the hypothesis that mammalian pets could harbor respiratory pathogens of relevance to disease exacerbation among inner-city children with asthma. Methods: We tested nasal and pharyngeal biospecimens from subset of 5–17 years old primarily African-American children with asthma enrolled in an ongoing cohort (ECATCh, NCT02251379) prior to trial randomization. At a home visit within three weeks prior to the clinic visit at which children were swabbed, mammalian pets whose owners consented to participate were sampled at nares, mouth, and perineum, depending on animal access and temperament. Aliquots (400 µL) of medium from Copan e-swabs from children and mammalian pets were cultured for multiple respiratory pathogens at the clinical microbiology laboratory at Johns Hopkins Hospital. Results: We evaluated 95 children with asthma and 60 mammalian pets at the baseline clinic and home visits, respectively. In children, carriage of respiratory pathogens was: Staphylococcus aureus, 36.8%; Moraxella catarrhalis, 8.4%; Group A Strep, 7.4%; Streptococcus pneumoniae, 1%. In mammalian pets, carriage of respiratory pathogens was: Moraxella catarrhalis, 11.7% (1 dog, 6 cats where 5 of the cats were in the same household); Streptococcus pneumoniae, 1.7% (1 dog). In the home where the dog carried Moraxella catarrhalis (perineum site), the child also carried Moraxella catarrhalis (nares site). Children with dogs had 8-fold higher odds of detection of Moraxella catarrhalis (95% Confidence Interval: 1.4, 46.9, P = 0.02), controlling for other pet ownership and demographic variables. Dogs had higher contact with child participants than cats (contact score higher by 0.7 points on average, P < 0.05). Conclusion: Mammalian pets may harbor respiratory pathogens, including Moraxella catarrhalis . Future studies are needed to determine the direction of transmission and whether mammalian pets can serve as a vehicle or reservoir of pathogens of relevance to respiratory disease in children. Disclosures: All authors: No reported disclosures.